Synergistic Effects of Bacillus amyloliquefaciens SDTB009 and Difenoconazole on Fusarium Wilt of Tomato - Xu, Xueming (Plant disease, 2022)
Fusarium wilt is a destructive and widespread disease of tomatoes in China, and currently, there are no effective and environmentally friendly control measures. Combining biological control agents with fungicides has become an executable method for disease control. Here, Bacillus amyloliquefaciens SDTB009 showed excellent in vitro antagonistic activity against Fusarium oxysporum and tolerance to high concentrations of difenoconazole (200 mg/liter) in vitro. The combination of SDTB009 and difenoconazole exhibited more effectiveness in mycelial growth inhibition than either treatment alone. Compared with that in the SDTB009 bulk solution in vitro (5.22 g/liter), surfactin titer reached 7.15 g/liter in the 100 mg/liter of difenoconazole-containing medium. Interestingly, the upregulation of 20 genes in the surfactin biosynthesis pathway from 2-fold to 4-fold was observed, explaining the synergistic effect. The SDTB009 combined with varying concentrations of difenoconazole (60, 120, and 150 g a.i./ha) showed a synergistic effect in two consecutive years of field trials. These results show that the integration of difenoconazole with the biocontrol agent B. amyloliquefaciens SDTB009 synergistically increases the control efficacy of the fungicide against tomato Fusarium wilt